Genetic polymorphisms in sex hormone metabolizing genes and drug response in women with epilepsy. (November 2010) - Grover, Sandeep; Talwar, Puneet; Gourie-Devi, Mandaville; Gupta, Meenal; Bala, Kiran; Sharma, Sangeeta; Baghel, Ruchi; Kaur, Harpreet; Sharma, Abhay; Kukreti, Ritushree
Aims: It is hypothesized that functionally relevant polymorphisms in genes encoding metabolizing enzymes of sex steroids may influence drug response by directly predisposing women with epilepsy to seizure exacerbation. An alteration in estradiol:progesterone ratio is believed to play a role in seizure occurrence in women. CYP1A1 is a key enzyme involved in the metabolism of estradiol, with variants of the CYP1A1 gene having been reported to play a role in the alteration of sex hormone metabolism in women. The objective of the present study was to test for the association of genetic variants in CYP1A1 with seizure recurrence in patients diagnosed with epilepsy.Materials & methods: In the study, the association of five variants in CYP1A1 with seizure control in 228 patients with epilepsy on first-line antiepileptic drug therapy for a minimum period of 12 months was investigated.Results: A significant association of an intronic SNP, IVS1 +606C>A (rs2606345), with respect to seizure recurrence (genotypic: p = 3.3 × 10 -4 ; allelic: p = 7.2 × 10 -4 ; OR: 2.86; 95% CI: 1.5–5.3) in women with epilepsy from North India was observed.Conclusion: Since CYP1A1 is not involved in the metabolism of any of the first-line antiepileptic drugs, these results imply that variants from genes encoding sex hormone metabolizing enzymes might act as markers for predicting response to antiepileptic drug therapy in women with epilepsy.